The Two-Faced Potato Virus X: From Plant Pathogen to Smart Nanoparticle - Lico, Chiara; Benvenuto, Eugenio; Baschieri, Selene (Frontiers in Plant Science, 2015)
Potato virus X (PVX) is a single-stranded RNA plant virus, historically investigated in light of the detrimental effects on potato, the world's fourth most important food commodity. The study of the interactions with cells, and more generally with the plant, both locally and systemically, significantly contributed to unveil the mechanisms underlying gene silencing, fundamental not only in plant virology but also in the study of gene expression regulation. Unraveling the molecular events of PVX infection paved the way for the development of different viral expression vectors and consequential applications in functional genomics and in the biosynthesis of heterologous proteins in plants. Apart from that, the ease of manipulation and the knowledge of the virus structure (particle dimensions, shape and physicochemical features) are inspiring novel applications, mainly focused on nanobiotechnology. This review will lead the reader in this area, spanning from fundamental to applied research, embracing fields from plant pathology to vaccine and drug-targeted delivery, imaging and material sciences. Due to the versatile moods, PVX holds promise to become an interesting nanomaterial, in view to create the widest possible arsenal of new “bio-inspired” devices to face evolving issues in biomedicine and beyond.